(untitled) (Heritage, 2025)
This paper examines irregular migration and human smuggling along the Western Balkans route through Serbia, providing a criminalistic and criminal law analysis of the offenses of illegal border crossing and human smuggling under Article 350 of the Criminal Code. Over the past decade, mass irregular migrations to economically developed European countries by individuals from certain Asian and African nations affected by armed conflicts—seeking to save their lives or escape threats to basic human rights, persecution, and poverty—have led to a rise in the number of human smuggling offenses in Serbia. The substantial illegal profits gained by human smugglers have fueled the development of organized criminal activities. Human smuggling has become the dominant criminal activity of many regional and international criminal groups. In many instances, these groups smuggle irregular migrants from their home countries to Western and Central European nations for a fee. Since 2011, one branch of the Western Balkan smuggling route, which crosses Serbia’s borders, has gained significant prominence, with the highest number of asylum seekers registered in 2015. In this paper we analyzed the actions of the Serbian police and judicial authorities in combating this type of crime from 2018 to 2023, with a particular focus on the penal policies of the courts in the period from 2018 to 2022. It has been established that the legislative penal policy has been tightened. Courts have limited ability to reduce sentences for more severe forms of this criminal offense. Human smugglers are most often sentenced to the minimum prescribed penalties, which are still lengthy prison sentences, thereby using measures of general prevention to deter potential offenders from committing such crimes. As a measure of special prevention, the law mandates the confiscation of motor vehicles used in the commission of a criminal offense. Smugglers face severe legal consequences if they are caught. Police measures are focused on repeat offenders, means of execution, and criminal hotspots, primarily in the areas along the state border with North Macedonia and Bulgaria, as well as Hungary and Croatia. Strategic documents have been adopted in which the suppression of human smuggling is recognized as a priority in the work of the police at the highest central level. Serbian police actively cooperates with regional and international police organizations (Interpol, Europol, Frontex, etc.) in order to suppress migrant smuggling. Modern technical equipment such as drones and thermal imaging camera are also used to monitor smuggling routes and detect smugglers and migrants who illegaly enter, transit through or exit Serbia. Detected human traffickers are often arrested. The proactive approach of the Serbian police has led to an increase in the number of arrests of organized crime group members as well as traffickers involved in more serious forms of this criminal offense. Considering the analyzed sentences, it has been determined that human smugglers are most frequently identified if they are at lower levels within criminal organizations. Those people are employed to transport migrants along specific routes. Given that a more severe form of the criminal offense is anticipated for those who smuggle a larger number of individuals, they are punished with long prison sentences, with a minimum of 2 years.